HIGHER ORDER THINKING SKILL (HOTS) LEARNING ASSESSMENT TRAINING IN ELEMENTARY SCHOOL - Rizal Rizal; Arif Firmansyah; Moh. Aqil; Surahman Wilade (Universitas Tadulako, 2021)
Community service is one form of the Tri Dharma of Higher Education that must be fulfilled by lecturers. Community service can be done in various forms of activities, but the most common is the sharing of knowledge and skills to improve the competence, capacity and performance of the target group (partners). For lecturers who concentrate on education, the target group is teachers and other educators. In this case, community service this time targets teachers at SDN 8 Banawa as partners. Based on the results of the situation analysis, in general, learning assessments are carried out based on assessment guidelines, but teachers have not innovated HOTS-oriented learning assessments in elementary schools. This community service aims to provide skills as well as understanding how to carry out HOTS-oriented learning assessments in elementary schools. The purpose of this community service is to improve the skills of teachers in HOTS-oriented learning assessment at SDN 8 Banawa. This activity is carried out in four stages, namely observation, training, mentoring and evaluation. Observations have been made before this proposal was drafted, while training is a process of transferring knowledge and skills in routine monthly activities that are on the teacher's agenda at SDN 8 Banawa, Banawa District, while mentoring will be carried out in schools when partner teachers apply the results of training in class. Evaluation was conducted to determine the applicability and effectiveness of the training results. Based on the evaluation results, it can be seen that teachers' knowledge about HOTS has increased, as evidenced by the results of interviews with teachers who have understood and understood what HOTS is. Whereas previously they were unfamiliar with the word HOTS or Higher Order Thinking Skill (HOTS). The skills of teachers have also improved, and they have been able to develop HOTS learning assessment instruments.